Effect of Crude Oil Polluted Water on the Haematology of Cockerel Reared under Intensive System - Akporhuarho , P.O. (International Journal of Poultry Science, 2011)
This study was designed to investigate the effect of polluted water on the Hematological indices of cockerels fed with polluted water at 5 ml, 10 ml and 15 ml of crude oil. The results showed that there was a significant difference (p